Tactile stimulation of young WAG/Rij rats prevents development of depression but not absence epilepsy - Balikci, Aymen; Eryilmaz, Ugur; Guler, Vildan Keles; Ilbay, Gul (Frontiers in Behavioral Neuroscience, 2024)
Investigations in Wistar Albino Glaxo from Rijswijk (WAG/Rij) rats that are susceptible to genetic absence epilepsy have demonstrated that environmental modifications affect absence seizures. Previously, we showed that neonatal tactile stimulations produce disease-modifying effect on genetically determined absence epilepsy and associated depression in Wag/Rij rats. The study presented here examined the effect of TS during late ontogenesis (adolescence and young adulthood) on epilepsy and depression outcomes in this genetically epileptic rat strain. On postnatal day (PND) 38, male WAG/Rij rats randomly were assigned to either the tactile stimulation (TS), handled or control group (unhandled) with 8 animals in each group. Following a 7-day adaptation period to their new surroundings, the animals were submitted to tactile stimulation from PND 45 to PND 90, five days per week, for 5 min daily. The tactile-stimulated rat was removed from its cage, placed on the experimenter’s lap, and had its neck and back gently stroked by the researcher. The handled rats were taken to another cage and left alone for 5 min daily from PND 45 to PND 90. The control rats were left undisturbed in their home cage, except for regular cage cleaning. After PND 90, all rats were left undisturbed until behavioral testing and EEG recording. When the animals were 7 months old, they were subjected to the sucrose consumption test (SCT) and the forced swimming test (FST). Electroencephalogram (EEG) recordings were made at 8 months of age in order to measure electroencephalographic seizure activity, thus, the spike–wave discharges (SWDs). Tactile-stimulated rats showed increased sucrose consumption and number of approaches to the sucrose solution in the SCT when compared with the handled and control rats. In the FST, rats in TS group showed lower immobility time and greater immobility latency, active swimming time and diving frequency than the handled and control rats. The duration and the number of seizures were not different amongst the groups. The data obtained suggest that TS in young rats is able to prevent depression in WAG/Rij rats.